2009
DOI: 10.1063/1.3247545
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the flux of high energy negative ions during reactive magnetron sputtering

Abstract: Articles you may be interested inInvestigation of ionized metal flux in enhanced high power impulse magnetron sputtering discharges J. Appl. Phys. 115, 153301 (2014); 10.1063/1.4871635 Current-voltage-time characteristics of the reactive Ar/O2 high power impulse magnetron sputtering dischargeThe negative ion flux during reactive sputtering from planar and rotating cylindrical magnetrons has been studied. Energy resolved mass spectrometry was used to measure the energy and mass distribution of the negative ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 34 publications
(33 reference statements)
3
33
0
Order By: Relevance
“…On the contrary, few works deal with negative ion surface-production in cesium-free plasmas 41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68 . Most of them are related to the industrial process of layer deposition by sputtering and concern mainly oxygen negative ions [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. H-surface-production in Cs-free plasmas has been mainly studied in 59, 60, 61, 62 (carbon materials), 63 (stainless steel), and 64,65,66,67,68 (barium surfaces).…”
Section: A-introductionmentioning
confidence: 99%
“…On the contrary, few works deal with negative ion surface-production in cesium-free plasmas 41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68 . Most of them are related to the industrial process of layer deposition by sputtering and concern mainly oxygen negative ions [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. H-surface-production in Cs-free plasmas has been mainly studied in 59, 60, 61, 62 (carbon materials), 63 (stainless steel), and 64,65,66,67,68 (barium surfaces).…”
Section: A-introductionmentioning
confidence: 99%
“…Consequently, formation of energetic negative oxygen ions appears likely also during sputtering from an Y 2 Si 2 O 7 target. Moreover, indication of YO and YO 2 [29,30] and SiO, SiO 2 , and SiO 3 [31] cluster formation was reported, which might be r.f. power dependent.…”
Section: Resultsmentioning
confidence: 96%
“…The Ba and Cu depletion in the thin films was suggested to be caused by resputtering by negative O À and O 2 À ions formed at the target surface and accelerated by the target potential. The formation of energetic negative oxygen ions during sputtering of Y [29,30] and Si [31] in a reactive Ar/O 2 was reported. Consequently, formation of energetic negative oxygen ions appears likely also during sputtering from an Y 2 Si 2 O 7 target.…”
Section: Resultsmentioning
confidence: 98%
“…It is interesting to notice that the monoclinic phase appears at mild oxygen pressure. Although the real mechanism for the observed results is still under investigation, the role of negative ion bombardment, relative to the deposition rate, can be expected to play a role [39]. Indeed, some authors reported on the presence of the monoclinic phase due to negative ion bombardment during the deposition of erbium sesquioxide [40].…”
Section: Thin Film Texturementioning
confidence: 84%